Sentinel hospital-based surveillance for norovirus infection in children with gastroenteritis between 2015 and 2016 in Italy. - Simona De Grazia; Gianvito Lanave; Giovanni Maurizio Giammanco; Maria Cristina Medici; Flora De Conto; Fabio Tummolo; Adriana Calderaro; Floriana Bonura; Noemi Urone; Anna Morea; Daniela Loconsole; Cristiana Catella; et al. (PLoS ONE, 2018)
Noroviruses are one of the leading causes of gastro-enteric diseases worldwide in all age groups. Novel epidemic noroviruses with GII.P16 polymerase and GII.2 or GII.4 capsid type have emerged worldwide in late 2015 and in 2016. We performed a molecular epidemiological study of the noroviruses circulating in Italy to investigate the emergence of new norovirus strains. Sentinel hospital-based surveillance, in three different Italian regions, revealed increased prevalence of norovirus infection in children (<15 years) in 2016 (14.4% versus 9.8% in 2015) and the emergence of GII.P16 strains in late 2016, which accounted for 23.0% of norovirus infections. The majority of the strains with a GII.P16 polymerase showed a GII.2 capsid genotype (79.5%). Also, a marked circulation of strains with a GII.17 capsid (14.0%) was observed, chiefly in early 2016. The emergence and global spread of non-GII.4 noroviruses pose challenges for the development of vaccine strategies.